Morfología de las especies de Hyphessobrycon (Characiformes: Characidae), grupo heterorhabdus, en Colombia - A. García-Alzate, Carlos (Universidad de Costa Rica, 2011)
Hyphessobrycon is the most numerous and morphologically complex genus of Characidae, and includes 18 species reported for Colombia, from which thirteen belong to the heterorhabdus-group different methods have been proposed for species identification within this genus. This study used these species to undertake a morphogeometric analysis by the Box Truss and Thin Plate Splin (TPS) methods; 13 homologous landmarks type I and three type II were used. The result of cluster analysis indicated that these species are represented by two big groups: robust and thin. The uniform and non uniform components, and the principal warps (WP) and partial warps (Wparc), described the shape changes related to body depth, involving relative displacements of the appendicular skeleton and the cephalic region. All species were characterized by allometric growth with the exception of Hyphessobrycon mavro, who presented an isometry between the landmarks 6-7. Two new measures are proposed for species discrimination in the group (snout-supraoccipital spine distance and supraoccipital spine-pelvic fin).